Stevia Rebaudiana Bertoni, Source of a High-Potency Natural Sweetener: A Comprehensive Review on the Biochemical, Nutritional and Functional Aspects - Lemus-Mondaca, R (2012)
Stevia rebaudiana Bertoni, an ancient perennial shrub of South America, produces diterpene glycosides that are low calorie sweeteners, about 300 times sweeter than saccharose. Stevia extracts, besides having therapeutic properties, contain a high level of sweetening compounds, known as steviol glycosides, which are thought to possess antioxidant, antimicrobial and antifungal activity. Stevioside and rebaudioside A are the main sweetening compounds of interest. They are thermostable even at temperatures of up to 200 °C, making them suitable for use in cooked foods. S. rebaudiana has a great potential as a new agricultural crop since consumer demand for herbal foods is increasing and proximate analysis has shown that Stevia also contains folic acid, vitamin C and all of the indispensable amino acids with the exception of tryptophan. Stevia cultivation and production would further help those who have to restrict carbohydrate intake in their diet; to enjoy the sweet taste with minimal calories. © 2011 Elsevier Ltd. All rights reserved.